Chirality of Light in Hybrid Modes of Vacuum-clad Ultrathin Optical Fibers - Kien, Fam Le; Busch, Th.; Truong, Viet Giang; Chormaic, Sıle Nic (Communications in Physics, 2017)
We investigate chirality of light in the quasicircularly polarized fundamental HE11 mode and the quasicircularly polarized higher-order hybrid modes of vacuum-clad ultrathin optical fibers. We show that, for a given fiber with the parameters in the range of experimental interest, the higherorder modes have smaller optical chirality per unit energy than the fundamental mode. The sign of the chirality per unit energy of a HE or EH mode is the same as or opposite to, respectively, the sign of the phase circulation direction. Outside the fiber, the fields in the quasicircularly polarized HE11 mode and the quasicircularly polarized higher-order HE21 and HE31 modes are superchiral.